Introduction: European Universities and Their Changing Roles and Functions - Kwiek, Marek (My University, 2013)
There are numerous and often interrelated causes of current transformations of European universities studied in this volume. First, globalization processes with their impacts on European nation states and public services these nation states have traditionally been guaranteeing to its citizens. Second, Europeanization processes, most often defined as a regional, European response to globalization and internationalization processes. Third, the large-scale (in theory, practice, or both) questioning of the foundations of the “Golden Age” of the Keynesian welfare state in the form it has been known in postwar Europe and largescale reforms (in theory, practice, or both) of the public sector in general and its particular public services. Four, demographic changes which affect or are expected to affect in the next few decades the majority of aging European societies. Five, the massification and (often) universalization of higher education and its increasing diversification across European systems. And, finally, the emergence of knowledge societies and knowledge-driven economies and the acknowledgement of the fundamental role universities play in new economic and social contexts. The above processes, except for demographics, have been culminating about a decade ago and have been accompanied by powerful, both national and supranational, discourses at various interrelated policy-making levels.
Keywords: university governance; university funding; complexity; public-private dynamics; European educational policies; policy convergence; higher education; public policy; European universities; transformations; university reforms; higher education reforms; university organization; organizational approach; university as organization; public sector; public trust; public sector services; academic profession; academic faculty; global trends; European trends; Europeanization; massification; universalization; globalization; demographics; university income